2021
DOI: 10.1038/s41598-021-86851-6
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial failure after hippocampal-avoidance prophylactic cranial irradiation in limited-stage small-cell lung cancer patients

Abstract: We evaluated intracranial failure after hippocampus-avoidance-prophylactic cranial irradiation (HA-PCI) for limited-stage small-cell lung cancer (SCLC). Data of 106 patients who received PCI with 25 Gy were retrospectively reviewed. The patients were divided into two groups based on whether they underwent HA-PCI: the HA-PCI group (n = 48) and the conventional PCI (C-PCI) group (n = 58). Twenty-one patients experienced intracranial failure: 11 and 10 patients in the C-PCI and HA-PCI groups, respectively. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Following these prospective clinical trials to confer neuro-cognitive protection in metastatic brain disease, HA-WBRT has gained clinical acceptance (7,8). However, perihippocampal failure has been reported from clinical observations (18)(19)(20). We have also reported unusual cases of intracranial failure following HA-WBRT therapy and perihippocampal failure rate was about 8% in…”
Section: Discussionmentioning
confidence: 91%
“…Following these prospective clinical trials to confer neuro-cognitive protection in metastatic brain disease, HA-WBRT has gained clinical acceptance (7,8). However, perihippocampal failure has been reported from clinical observations (18)(19)(20). We have also reported unusual cases of intracranial failure following HA-WBRT therapy and perihippocampal failure rate was about 8% in…”
Section: Discussionmentioning
confidence: 91%
“…The landmark NRG Oncology CC003 study conducted in the United States reported an intracranial relapse rate of 14.2% at 12 months (18), while an investigation conducted in South Korea reported a relapse rate of 20.8% (19). However, the rate of intracranial failure in that study did not differ significantly between conventional PCI and HA-PCI groups, and no clinical factor was found to be associated with the intracranial failure (19). In our study, the bilateral hippocampal volumes following HA-PCI did not decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al reported 48 patients with SCLC who underwent HA-PCI; 2 developed perihippocampal recurrence. It was suggested that HA-PCI may be associated with an increased risk of intracranial failure, whereas HA-PCI did not impair disease control or survival [20] . Redmond et al reported 20 patients with SCLC who received HA-PCI; 2 patients developed metastases in the under-dosed region, 1 on the dentate gyrus and 1 around the HA region [27] .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that HA-PCI may be associated with an increased risk of intracranial failure, whereas HA-PCI did not impair disease control or survival. [ 20 ] Redmond et al reported 20 patients with SCLC who received HA-PCI; 2 patients developed metastases in the under-dosed region, 1 on the dentate gyrus and 1 around the HA region. [ 27 ] A phase 3 randomized trial of PCI with or without HA in SCLC concluded no difference was observed between the arms in the incidence of brain metastasis or in overall survival rates, neither in patients with stages I to III or stage IV disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation